Obcokulturowe antroponimy w przekładzie rosyjsko-polskim w kontekście indywidualnego podejścia tłumacza - Jóźwiak, Jolanta (Studia Rossica Posnaniensia, 2016)
The paper deals with the problem of rendering personal names from foreign cultures into Russian and Polish. An individual approach is required from the translator in every separate case because of the distinctions in the perception of these culturally-determined elements. There are many situations when the modification of standard translation procedures is required, particularly when the unit is used in an unusual function. Irrespective of the orientation to form or meaning, the reactions of readers and potential associations are the most important.